Physicochemical and microbiological characterization of “New Zealand” rabbit meat and effect of marinating with CaCl2 - Herrera-Stanziola, Javier (2023)
Introduction. Rabbit meat has a high nutritional value, but its texture, toughness, and color impact consumers’ purchasing decisions, therefore making an improvement is desirable. Objective. To perform a physical, chemical, and microbiological characterization of rabbit (Oryctolagus cuniculus) meat and determine the effect of CaCl2 application on its quality. Materials and methods. In San José, Costa Rica, between January and September 2015, pieces of rabbit thigh marinated and unmarinated with CaCl2, cooked and uncooked, were analyzed both at initial time and after five days of storage. A complete proximal analysis and microbiological plating tests, pH measurement, drip loss determination, and color and texture measurement were performed. Results. The meat had a moisture content of 75.3 %, 2.8 % fat, 21.1 % protein, and 0.8 % ash. The proteins were distributed as 54.8 % sarcoplasmic, 35.1 % myofibrillar, and 10.1 % (SD=1.05) stroma. There were no significant differences in pH measurements. An initial load of psychrophilic organisms from abiotic sources was found. Regarding drip loss, unmarinated meat had a value of -1.0±0.7 %, and marinated meat had value of -0.1±0.6 %. The addition of CaCl2 produced a whiter meat; but after cooking, it had a more yellow color. No significant differences were found in tenderness when CaCl2 was added. Conclusions. The quality of the rabbit meat obtained was comparable to that reported in the literature. The addition of CaCl2 by marinating had no effect on the overall quality of rabbit meat under the conditions of the present study.